Lost and found : recovering regional identity in imperial Japan - Shimoda, Hiraku, 1972- (Harvard East Asian monographs ;, 2014)
"Offers a new understanding of modern Japanese regionalism by revealing the volatile historical relationship between region and nation in the late nineteenth and early twentieth centuries. Aizu becomes a case study for how one locale was estranged from nationhood for its treasonous blunder in the Meiji Restoration, yet eventually found a useful place within the imperial landscape"--